Analisis Kesesuaian Harapan Mahasiswa dengan Persepsi Manajemen pada Program Studi Manajemen di Daerah Istimewa Yogyakarta - Kusuma Chandra Kirana (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2016)
Abstract The key success in winning the competition is the ability to achieve the objectives in creating and maintaining the customers. Therefore, the management of the program has to satisfy the customers. One way to obtain the customer satisfaction is to deliver a quality service required by the customers. It means that the management of the business schools need to have a good understanding on students need that there is no gap between the expectation of the students and the service they received. Thus, the understanding of their need is highly required the quality service can be provided. Based on the result of the study that the processed using servqual analysis instrument, the hierarchy and correlation ranking, there is a significant difference between consumers expectation in School of Management in Yogyakarta.